Efeitos da disposição de lodo de ETE de indústria alimentícia no solo: estudo de caso - Pereira, Ana Carolina Amaral [UNESP] (2015)
Sludge from wastewater treatment plants usually contains high levels of organic matter and nutrients, and therefore it can be used as fertilizer and soil conditioner. However, its disposal on the soil has to be properly managed because it can contain contaminants and pathogens. The aim of this work was to study the effects of food industry sludge disposal on the soil and groundwater, as well as to assess the sludge application viability. The results show that the sludge characteristics are adequate for its application on latosol according to brazilian federal regulation (Resolução CONAMA nº 375/2006), but it must be treated prior to the land disposal to reduce the pathogens levels. All soil and groundwater parameters met the constituents' quality standards settled by brazilian federal regulation (Resolução CONAMA nº 420/2009), and there was no statistically significant difference for toxic organic substances between the amended and unamended soil treatments. There was a small concentration increase of inorganic compounds (Al, Ba, B, Co, Cu, Fe, Mn, Ni, Zn) in the soil area with sludge, but it was not statistically confirmed. Soil fertility, sum of bases, cation exchange capacity, and organic matter values increased with sludge application, and exchangeable Al and Al saturation values decreased